Developing theory and evidence based intervention content using the Behaviour Change Wheel, Theoretical Domains Framework, and the Person-Based Approach: A worked example for an intervention targeting sedentary behaviour with people living with obesity - Fiona Curran; James Matthews; Gráinne O’Donoghue (PLoS ONE, 2025)
Introduction Both sedentary behaviour and obesity are independent risk factors for poor health and quality of life. Reducing sedentary behaviour is an important public health strategy. People with moderate or severe obesity have unique challenges to reducing sedentary behaviour. The Behaviour Change Wheel (BCW) and the Person Based Approach (PBA) are complementary frameworks for intervention development aligned to these concepts. This article describes the development of content for an intervention which aims to reduce sedentary behaviour during leisure time in the domestic domain among people living with moderate or severe obesity. Methods The BCW and PBA guided the development of the intervention content, using in-depth qualitative data with people living with obesity (n = 21). A detailed behavioural analysis conducted using the Capability, Opportunity and Motivation Behaviour (COM-B) model and Theoretical Domains Framework (TDF) provided the data for selecting appropriate content for the target user group. Content was selected using the Behaviour Change Techniques Taxonomy (BCTTv1), Theory and Techniques Tool, two systematic reviews, and key scientific literature. Results Twenty two behaviour change techniques with potential to change SB in the domestic domain were identified, which can be delivered remotely via an online intervention. Intervention functions consist of education, persuasion, training and enablement. Strategies and guiding principles are outlined. A SB example for all 93 BCT’s in the BCTv1 is provided alongside a longlist of 50 more relevant BCTs to serve as a reference guide for future designers. Conclusion A theory, evidence and person-based approach to develop an intervention to reduce sedentary behaviour in the domestic domain for people living with obesity is described. The BCW guide, COM-B model, TDF and BCT-Taxonomy provided the framework for selection of theoretical content. To ensure relevance for the target population, the content and mode of delivery was developed in collaboration with people with moderate to severe obesity using the PBA.